Design of a Sensor System to Digitize Manual End Milling Machine to Collect Machine Data - Chan, Choon Kit; Chong, Shin Hau (INTI International University, 2020)
In the manufacturing system, machines and manufacturing data are becoming more closely linked. In order to collect manufacturing data, there have been many new technologies that are in line with the Industrial Revolution 4.0 to replace existing systems and machines. The objective of this study is to design a sensor system that can collect and stream machine data from an end milling machine to generate a manufacturing report. A prototype of this system was designed using a Raspberry Pi Model 3 B+, PiCamera module, and infrared sensors for installing onto the machine, while Microsoft Azure and Power BI were used to stream and publish the data in a report form. The design was placed onto a milling machine where a machinist had done one milling operation for one workpiece, the sensors collected the data of X-position, Y-position, feed rate, and spindle speed, while deriving the percentage utilization of total time for cutting steps. The end result was a system that was integrated with the milling machine where the critical operation data are collected to produce a manufacturing report that displays the use of the machine. For future studies, different applications for this kind of sensor system can be used to digitize different manufacturing systems. Furthermore, an optimization and standardization testing for this kind of manufacturing system could be set in the future as well.